Analytical chemistry. Electrochemical methods of analysis: study aid - Korotkova E. I. Elena Ivanovna; Voronova O. A. Olesya Aleksandrovna; Dorozhko E. V. Elena Vladimirovna; Lipskikh O. I. Olga Ivanovna (Tomsk, Tomsk Polytechnic University Publishing House, 2021)
Заглавие с титульного экрана